LAYANAN PERPUSTAKAAN DI ERA MILLENIAL - Jepri (Sekolah Tinggi Ilmu Tarbiyah (STIT) Lingga, 2023)
The existence of a library as a source of information and learning center must be optimized. Quick access to information and accuracy are the main strengths of a library in serving millennial users. Conventional library services that are rigid must be changed. The demand for instant, precise access to information and the availability of applied facilities will represent the information service system served by the library. Libraries must provide technological devices that allow users to easily surf for information via the internet. It is time for libraries to start changing the atmosphere of the library so that it becomes a learning center for its community. Providing wholehearted service is the main key for librarians in providing services to users. This is what is always expected and longed for by users in the millennial era. The task of the library is to create a millennial generation that is smart in responding to any changes that will and continue to occur. This task will be one of the big tasks for librarians to always be quick to present and precise in providing information for every service for them. The characteristics of millennial users need to be understood by libraries with varied services that can support millennial generation activities.